2011
DOI: 10.1002/bdrb.20292
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to diclofenac disturbs actin organization and leads to myofibril misalignment

Abstract: The objective of this study was to investigate the embryotoxicity of diclofenac. Zebrafish (Danio rerio) embryos at 12 hpf were treated with different dosages of diclofenac (0-2,000 ppm) for different time courses (12-72 hr). Results showed no evident differences in survival rates or morphological changes between the mock-treated control (0 ppm) zebrafish embryos and those with 1-ppm diclofenac-exposure (12-24, 12-36 hpf). In contrast, after higher doses (5 and 10 ppm) of exposure, embryos displayed some defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
5
0
2
Order By: Relevance
“…Furthermore, previous acute toxicity studies on NVK by Anbarasu et al (2011) revealed that the ethanolic extract of NVK did not show mortality and toxic signs up to 2000 mg/kg and supports its indication for various fevers such as dengue and chikungunya fever as it had antipyretic, anti-inflammatory, and analgesic activity in experimental mice models [22]. Furthermore, there were no adverse effects reported in the earlier clinical studies on NVK administration both in adults [23] and pediatric population [24][25][26]. Thus, the present study results are found to be in concordance with the in vivo animal and human data of previous studies.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, previous acute toxicity studies on NVK by Anbarasu et al (2011) revealed that the ethanolic extract of NVK did not show mortality and toxic signs up to 2000 mg/kg and supports its indication for various fevers such as dengue and chikungunya fever as it had antipyretic, anti-inflammatory, and analgesic activity in experimental mice models [22]. Furthermore, there were no adverse effects reported in the earlier clinical studies on NVK administration both in adults [23] and pediatric population [24][25][26]. Thus, the present study results are found to be in concordance with the in vivo animal and human data of previous studies.…”
Section: Discussionsupporting
confidence: 63%
“… In relation to diclofenac exposure to zebrafish ( Danio rerio ), it was previously shown that actin organization and muscle fibre alignment are disturbed thereby inducing a malformed somite phenotype. Isocitrate dehydrogenase (id: 482), as part of the Krebs cycle, is very involved in energy metabolism and significantly decreased in abundance here. It has previously been suggested to play a role in antioxidant defence.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for antibody labeling, F‐actin staining, whole mount in situ hybridization and cryosectioning have been described previously (Chen et al ., , ; Ding and Chen, ; Lee et al ., ). Aside from these methods, F59 (Hybridoma Bank, Iowa IA, USA) and rabbit polyclonal anti‐laminin (Sigma‐Aldrich) were used as primary antibodies, and myod (NM_131262) was used as a probe.…”
Section: Methodsmentioning
confidence: 97%